Mirizzi Syndrome Type IV: A challenging diagnosis - Navarini, Daniel; Scussel Madalosso, Carlos Augusto; Reffatti, Diego; Guareschi, Luma; Schmitt, Ana Paula; Marx, Guilherme; Jaskulski, Paula; Ribeiro, Henrique; Laydner, Thalis (Clinical and Biomedical Research, 2016)
Mirizzi Syndrome type IV is an extremely rare condition, which is confused with the diagnosis of cholangiocarcinoma in many cases. This report describes a case of a forty-three-year old patient, who was forwarded to our department of general surgery with a high suspicion of a choledochal neoplasic lesion. During the hospitalization he was diagnosed with Mirizzi Syndrome type IV. We concisely describe the case and the literature review about this pathology.